Analisis Komparatif Alih Fungsi Objek Wakaf Perspektif Fikih Mazhab Syafi’i dan Mazhab Hambali - Ahmad Syaifuddin (Isti`dal : Jurnal Studi Hukum Islam, 2021)
This study aims to understand the views of the Syafi'i and Hambali Schools about the conversion of the object of waqf and understand the comparison of the views of the two schools. This research uses descriptive normative method, qualitative research type, descriptive analysis approach. Data collection methods are primary data and secondary data. The results of this study are that, first, in the Syafi'i school, it is not permissible to sell waqf objects in the form of mosques on the grounds that the land can still be used for prayer and iktikaf, while the object of waqf other than mosques there are still differences of opinion among the Syafi'i schools themselves, some allow some are not. According to the Hambali school, it is not permissible to sell the object of waqf, but if the object of waqf is no longer useful, it can be sold even if it is a mosque. Second, the meeting point of the two schools of thought is that basically it is not permissible to sell the object of waqf because of its eternal nature, however, the Hambali school adds that if it can still be used, if it cannot then it can be converted or sold so that it can bring benefits and benefits as the purpose of waqf.